Islam beyond borders the umma in world politics - Piscatori, James P.; Saikal, Amin 1950 (Cambridge University Press, 2019)
The prospect of a united Muslim world has long inspired both dreams and fears. Many Muslims regard the pan-Islamic community, the umma, as the embodiment of the spiritual kinship of the faith, but it has also often been assumed to be inherently antagonistic to adherents of other faiths. Questions over relations with the Other are mirrored by debates over what constitutes the acceptable contours of Islamic doctrine itself. Indeed, the umma has had variant and contested meanings over time, and divergent perspectives on its inclusiveness or exclusiveness and whether it must have concrete or institutional form have become acute. The rise of jihadist movements has especially brought these related issues to the fore, with the targeting of external and internal 'enemies' presented as part of a purifying and defensive mission to rescue the umma from its current degradation. The anthem of the Islamic State of Iraq and Syria (ISIS), 'My Umma, Dawn Has Appeared', extols Muslims to give up this life in order to revive the umma and assure victory for Islam. The idea of the umma, so central and yet so elusive, has taken on a talismanic quality